The Effect of Problem-Solving Learning Model on Students’ Critical Thinking Skills in High School Physics Learning - Al Yamani, Reza Rahmiyatul Najwa; Susanna; Ahmad Farhan; Abdul Hamid; Ngadimin (Universitas Muhammadiyah Makassar, 2026)
Critical thinking is an essential competence in 21st-century physics learning, particularly because students are expected not only to memorize formulas but also to analyze scientific phenomena, evaluate evidence, and construct logical explanations. However, physics instruction in high schools often remains dominated by teacher-centered practices that provide limited opportunities for students to develop higher-order thinking skills. This study aimed to examine the effect of the problem-solving learning model on high school students’ critical thinking skills in learning about static fluids. A quantitative, pre-experimental one-group pretest–posttest design was employed. The participants were 24 Grade XI Science students at SMA Negeri 15 Adidarma Banda Aceh, selected through purposive sampling. Data were collected using an essay-based critical thinking skills test developed based on five indicators: elementary clarification, basic support, inference, advanced clarification, and strategy and tactics. The data were analyzed using descriptive statistics, N-Gain, paired sample t-test, Cohen’s d, and eta squared. The results showed that students’ average critical thinking score increased from 38.33 in the pretest to 80.71 in the posttest, with an average N-Gain of 0.70, categorized as high. The paired-samples t-test indicated a significant difference between pretest and posttest scores (p = 0.000 < 0.05). The effect size analysis showed a Cohen’s d value of 3.91 and an eta squared value of 0.97, indicating a very strong practical effect. The novelty of this study lies in providing empirical evidence on the application of problem-solving learning in static fluid material. These findings contribute to physics education by confirming that structured problem-solving instruction can effectively promote students’ critical thinking and meaningful conceptual understanding.